Harmonic reduction techniques in renewable energy distribution systems using cascaded multilevel inverters: a comparative analysis - Gangadhara, Nayana; Torvi, Savita D. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
Penetration of renewable energy in distribution generation increases power quality in the output. The harmonics inherent in the inverters are a major contributor to the power quality issues in the distribution system. Multilevel inverters are used to get rid of the harmonics inherent in the inverter output. Among the multilevel inverter topology cascaded multilevel inverters have taken center stage due to their simple topology and control with lesser components. This paper reviews different multilevel inverter topologies that have led to cascaded multilevel inverter topology and applies pulse width modulation (PWM) techniques to the topology. Phase disposition PWM technique is applied on the cascaded H-bridge multilevel inverter (MLI) topology for 5-level, 7-level, and 9-level inverter topologies. The total harmonic distortion (THD) obtained for these topologies is compared with and without the use of an LC filter in the inverter output. PWM techniques including phase disposition, for five-level, seven-level, and nine-level MLI methods are applied on the cascaded multilevel inverter and results are compared for harmonic reduction in the inverter output.